Hubungan Fiqih, Kalam, dan Tasawuf dalam Pandangan Thariqat Qadiriyah Wa Naqsyabandiyah Suryalaya Tasikmalaya - Jamaludin, Jamaludin; Rahayu, Solihah Sari (Prodi Hukum Ekonomi Syariah (Muamalah), 2023)
This research explains the relationship between the practice of fiqh, kalam and Sufism in the community of TQN Suryalaya. The approach used is juridical-normative with qualitative research methods. Qualitative data sourced from reference books of Tarekat Qadiriyah wa Naqsyabandiyah Suryalaya community. The results of the study found that phenomenologically, the religious life of the TQN Suryalaya community describes the events of obedience and legal awareness that reflect the identity of esoteric and exoteric rites of Islamic teachings. Most of them are carried out based on a strong awareness and belief that it can be a medium to achieve the potential and high purpose of life, namely insan kamil or akhlak karimah. The form of relationship between the understanding of the Tarekat Qadiriyah wa Naqsyabandiyah Suryalaya community in relation to the practice of the integration of fiqh, kalam and Sufism is at-Tadaruj (tiered and sequential unity) seen in six main teachings, namely: First, Talqin; Second, Miftah al-Shudur; Third, Uquudul Juman; Fourth, the book Akhlakul Karimah Akhlakul Mahmudah, based on Mudawamatul Dhikr. fifth, the Book of Worship as a Method of Guidance for Victims of Drug Abuse and Juvenile Delinquency; and sixth, tanbih.